Language of smell: Tracing some cross-cultural insights from past and present - Sharma, Chetan (Frontiers in Food Science and Technology, 2023)
It is assumed that the human sense of smell is inferior to vision. This framework of underdeveloped human olfaction can be mainly attributed previously to its historical demotion of it by the Western, quasi-scientific ideas, and evolutionary narratives or differences in reference to other animals, such as rats or mice. However, this notion of a comparatively poor sense of smell may have derived from the narrowly focused pseudoscientific practices of the past and needs to be revisited under more recent findings. Similarly, the generalization of language as poorly connected with the olfactory system needs more cross-cultural references to support or abolish this hypothesis. Humans’ olfactory system is not inferior, but certainly different from other species and humans have excellent olfactory abilities. Humans are exceptional in detection and discrimination; in fact, they are more sensitive than rodents and dogs to some odors. Language does not constrain the naming of odors due to cognitive architecture, and the mapping of language on the senses is culturally related. Jahai hunter-gatherers were found naming odors as easy as colors. Plasticity and culture were found to have a huge influence on odor naming. No universal hierarchy of senses, such as if vision is more codable than odor, was found imposing on languages.